Soft Landing in the Monetary Policy of the USA and the Euro Area - Petkova, Anika (Research Papers, 2025)
The current research examines the implementation of a "soft landing” in the monetary policies of the United States and the euro area, in particular the transition from contractionary to expansionary monetary policy due to the achievement of an inflation rate close to the target of two percent. The aim of the "soft" policy measure is to prevent a potential future recession by limiting the accelerated increase in the unemployment rate and the decline in the real economic growth rate.